Medieval manuscripts. Ghent University Library - Derolez, Albert, 1934-; Defoort, Hendrik, 1972-; Vanlangenhove, Frank (Gent : Snoeck Ducaju & Zoon, 2017)
This is the first catalogue to provide metadata on all medieval manuscripts in the collection of Ghent University Library. The catalogue offers full discriptions of texts and provides codicological data for all handwritten books and archival documents on parchment or paper, including fragments, dating prior to c. 1530. Giving all the essential information in a nutshell and in a uniform way opens numerous ways to new research with these unique relics. Albert Derolez (1934) is Curator emeritus of Manuscripts and Early Printed Books at Ghent University Library. He taught for many years palaeography and codicology at the Free Universities of Brussels and at several American universities. President of the Comité International de Paléographie Latine 1995-2005. Editor-in-Chief of the series Corpus Catalogorum Belgii. The Medieval Booklists of the Southern Low Countries (1994-2016). Editor of the Liber Floridus of Lambert of Saint-Omer (1968), the Liber divinorum operum of Hildegard of Bingen (1996), and other medieval texts. Author of books on medieval libraries, codicology and palaeography.
Met afbeeldingen uit de collectie Middeleeuwse handschriften van de Universiteitsbibliotheek Gent